2017
DOI: 10.1002/bmc.4082
|View full text |Cite
|
Sign up to set email alerts
|

Employment of modified Fe3O4 nanoparticles using thermo‐sensitive polymer for extraction and pre‐concentration of cefexime in biological samples

Abstract: Cefexime is a useful antibiotic that can be prescribed to treat bacterial infections. Nanoparticles have been widely marketed as a universal solution among scientists. Many studies have been performed to modify nanoparticles to make them functional as extraction and pre-concentration agents and drug carriers. Temperature-sensitive polymers belong to a group of substances that undergo a major change in their physical features in response to temperature. Recently developed polymers can be used in many different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Figure 5(a) also shows the FTIR spectrum of bare Fe 3 O 4 NPs. Three notable bands this spectrum included a broad band at 3327.01 cm −1 characterized by an OH-stretching vibrational mode, a band at 1637.37 cm −1 which is related to the stretching mode of O–H and the one at 543.24 cm −1 indicating the Fe–O stretching vibration (Naghibi et al , 2017). The Figure 5(b) and 5(c) are the FTIR spectra images of chitosan-coated Fe 3 O 4 nanoparticles (MCS-20 and MCS-25).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5(a) also shows the FTIR spectrum of bare Fe 3 O 4 NPs. Three notable bands this spectrum included a broad band at 3327.01 cm −1 characterized by an OH-stretching vibrational mode, a band at 1637.37 cm −1 which is related to the stretching mode of O–H and the one at 543.24 cm −1 indicating the Fe–O stretching vibration (Naghibi et al , 2017). The Figure 5(b) and 5(c) are the FTIR spectra images of chitosan-coated Fe 3 O 4 nanoparticles (MCS-20 and MCS-25).…”
Section: Resultsmentioning
confidence: 99%
“…Naghibi et al developed a modified Fe 3 O 4 adsorbent employing a thermo-sensitive polymer for the purpose of extracting and quantifying cefexime in biological samples [82]. In the present inquiry, the process of the co-polymer grafting of PNVCL and 3-allyloxy-1,2propanediol as a thermo-sensitive agent was executed on the surface of Fe 3 O 4 NPs.…”
Section: Dual-and Multi-stimuli-responsive Adsorbentsmentioning
confidence: 94%
“…The adsorbent demonstrated a reasonable rate of extraction recovery for cefexime from both plasma and urine samples, ranging from 71 to 89%. Moreover, the authors observed that the proportion of cumulative cefexime release at 37 • C was considerably greater compared to what occurred at 25 • C. They linked their findings to the deformation of the PNVCL chain on the surface of the adsorbent particles, which changes from a sharp coil to a globule shape when temperature exceeds the LCST limit [82].…”
Section: Dual-and Multi-stimuli-responsive Adsorbentsmentioning
confidence: 97%